2021
DOI: 10.1016/s2666-7568(21)00092-1
|View full text |Cite
|
Sign up to set email alerts
|

Observed and expected serious adverse event rates in randomised clinical trials for hypertension: an observational study comparing trials that do and do not focus on older people

Abstract: Background Representativeness of antihypertensive drug trials is uncertain, as many trials recruit few or no older people. Some trials specifically recruit older participants to address this. Here, we assess the representativeness of trials focusing on older people by comparing the rates of serious adverse events in these trials with the rates in trials of a general adult population (ie, standard trials), and comparing these findings to the rate of hospitalisations and deaths in people with hypertension starti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Indeed, one systematic review of 50 studies of trial inclusion and exclusion criteria encompassing 305 trials and 31 physical conditions found that more than half of the trials excluded more than half of patients with the conditions studied 241 . Even patient cohorts in trials that are specifically conducted in older people are likely to significantly differ from the clinical population 242 owing to explicit and implicit exclusion criteria or biases in trial recruitment (such as exclusion of house-bound individuals and those in care homes) 243 . These issues suggest that while treatment benefits observed in trials may be generally applicable to those with multimorbidity, the precise benefit in populations excluded from clinical trials may differ owing to varying baseline risk 244 or increased treatment harms 245 .…”
Section: Evidence-based Clinical Guidelinesmentioning
confidence: 99%
“…Indeed, one systematic review of 50 studies of trial inclusion and exclusion criteria encompassing 305 trials and 31 physical conditions found that more than half of the trials excluded more than half of patients with the conditions studied 241 . Even patient cohorts in trials that are specifically conducted in older people are likely to significantly differ from the clinical population 242 owing to explicit and implicit exclusion criteria or biases in trial recruitment (such as exclusion of house-bound individuals and those in care homes) 243 . These issues suggest that while treatment benefits observed in trials may be generally applicable to those with multimorbidity, the precise benefit in populations excluded from clinical trials may differ owing to varying baseline risk 244 or increased treatment harms 245 .…”
Section: Evidence-based Clinical Guidelinesmentioning
confidence: 99%
“…Another study found higher rates of SAEs in a UK psoriasis registry than in IPD from two psoriasis trials, even after re-weighting the register data to more closely resemble the trial populations [19]. Our own previous study also compared SAE rates in trial participants and patients in routine care finding higher rates in the routine care population after age-sex standardisation, but did so solely for trials of agents acting on the renin-angiotensin-aldosterone system in order to treat hypertension [9]. The current study adds to this somewhat sparse literature by examining the trial age-sex standardised observed/expected SAE ratio across a wide range of index conditions.…”
Section: Comparison With Other Studiesmentioning
confidence: 89%
“…SAE rates may therefore be utilised to help assess trial representativeness. In trials for hypertension, we tested this hypothesis, finding that the SAE rates were consistently lower than predicted based on hospitalisation and death rates among people with hypertension in routine care [9]. We also found that although SAE rates were higher in hypertension trials which aimed to be representative of older people, the rates were still lower than in routine care.…”
Section: Introductionmentioning
confidence: 85%
“…Even trials of antihypertensive therapy in older people tend to be targeted at healthier populations, less likely to have frailty, multi-morbidity and polypharmacy, excluding those with limited life expectancy [ 16 ]. Indeed, a recent analysis comparing participants in trials of antihypertensive therapy to similar patients residing in the community, found much lower rates of serious adverse events reported in trials, suggesting that these patients were fitter and healthier than the general population [ 17 ]. As a result, physicians have very little information about the benefits and harms of treatment in older people with multi-morbidity and frailty.…”
Section: Understanding the Benefits And Harms Of Antihypertensive Tre...mentioning
confidence: 99%